Particle breakage in granular soils: a review. (2nd January 2021) - Yu, Fangwei
Abstract: This paper presents a review of particle breakage in granular soils by comprehensively summarizing the measurement of particle breakage, the fundamentals of particle breakage, the soil mechanics on particle breakage, the theoretical models of soil incorporating particle breakage. In the measurement of particle breakage, most particle breakage indexes were proposed according to the change of soil grading. The increase in the particle-surface area and probabilistic method were also employed to quantify particle breakage. In the fundamentals of particle breakage, the crushability of granular soil is mainly related to the physical nature and mechanical properties of soil, the stress-strain state on soil and the surrounding environment on soil, which were always interpreted by the energy theory and fractal theory. In the soil mechanics on particle breakage, particle breakage resulted in impairment of dilatancy behavior of soil to become a more contractive soil, significantly influencing the shearing, dilatancy, and state behavior of soil. A number of constitutive models of granular soils incorporating particle breakage were proposed by the elastoplastic theory, the bounding surface theory, the disturb state concept theory, the continuum breakage mechanics theory, and the generalized plasticity theory for interpreting the influence of particle breakage on soil behavior.